Characterization of PAN-based Activated Carbon Fibers with Deposited Metal-Nanoparticles for Enhanced Wound Healing - Soares, Jéssica da Silva Gil (2022)
Tese de mestrado integrado, Engenharia Biomédica e Biofísica (Biofísica Médica e Fisiologia de Sistemas), 2022